STEM education in the Global North and Global South: competition, conformity, and convenient collaborations - Mudaly, Ronicka; Chirikure, Tamirirofa (Frontiers in Education, 2023)
We are science teacher educators who are collaborating on a science, technology, engineering, and mathematics (STEM) education project. The first author, an African man, is an academic who has studied, worked, and lived in four different third world countries. The second author is an Indian woman academic who works at a South Africa higher education institution. We have shared experiences of marginalisation based on race, ethnicity and socioeconomic status, and currently live in postcolonial societies which are plagued by social, economic and political uncertainty. Within this context our commitment towards a social justice approach in STEM education developed. Although we are critical of cognitive injustice which fuels socio-political and economic injustice, we are aware of our own complacency, complicity and conformity in our work which is located within the corpus of